2016
DOI: 10.1007/7651_2016_327
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol-Based Cell Therapy for Treatment of Lung Diseases

Abstract: Aerosol-based cell delivery technique via intratracheal is an effective route for delivering transplant cells directly into the lungs. An aerosol device known as the MicroSprayer(®) Aerosolizer is invented to transform liquid into an aerosol form, which then can be applied via intratracheal administration for drug delivery. The device produces a uniform and concentrated distribution of aerosolized liquid. Using the capability of MicroSprayer(®) Aerosolizer to transform liquid into aerosol form, our group has d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Nevertheless, the environment in the hospital has to be appropriately managed for inhaled administration of a treatment in COVID-19 patients. A number of studies have demonstrated the feasibility of delivering stem cells via spray for direct pulmonary delivery with high viability (Kardia et al, 2016;Kim et al, 2016;Skolasinski et al, 2020). Inhalation route of stem cell administration is an opportunity for efficient delivery of stem cells directly to the lungs, yet it remains an under-explored research area in the field.…”
Section: Is the Treatment Efficacy Dependent On The Delivery Route?mentioning
confidence: 99%
“…Nevertheless, the environment in the hospital has to be appropriately managed for inhaled administration of a treatment in COVID-19 patients. A number of studies have demonstrated the feasibility of delivering stem cells via spray for direct pulmonary delivery with high viability (Kardia et al, 2016;Kim et al, 2016;Skolasinski et al, 2020). Inhalation route of stem cell administration is an opportunity for efficient delivery of stem cells directly to the lungs, yet it remains an under-explored research area in the field.…”
Section: Is the Treatment Efficacy Dependent On The Delivery Route?mentioning
confidence: 99%
“…Microsprayer aerosolizer is a quantitative aerosol drug delivery device for small animals that has been used in several studies (Figure 4f). [ 26 ] As can be seen from Figure 4g,h, RDSV‐NE‐AYQ particle size and PDI were not affected after atomization either with PARI BOY or with the microsprayer aerosolizer.…”
Section: Resultsmentioning
confidence: 87%
“…For example, when MSCs and MSCs-Exo were injected into pneumonia patients, the pertaining trials exhibited nearly similar therapeutic effects [ 54 , 55 ]. On the other hand, cell-based inhalation therapy for treating lung infections has also progressed to clinical trials [ 56 , 57 ]. Additionally, some studies have suggested the immunomodulatory effects of MSCs and MSCs-Exo.…”
Section: Immunomodulation By Mesenchymal Stem Cells And/or Their Ementioning
confidence: 99%